Effect of fitness exercise on risk assessment of mental and emotional health - Zhaoliang Yang; Xiaoming Fu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The study aims to investigate the effect of physical activity on risk assessment for mental and emotional health. This paper studies the psychological test assessment through the psychological health risk assessment and psychological crisis intervention for college students and the psychological health crisis counselling risk assessment system. Experiments show that the evaluation accuracy of the designed system can reach 99% at most, and the detection time is at least 5S, which improves the evaluation performance. Based on the evaluation and with an emphasis on prevention, we will deconstruct the connotation of life education, build and operate a college students' mental health early warning system, and scientifically adopt psychological crisis intervention strategies and technologies to establish a college students' psychological crisis intervention mechanism and to promote and maintain college students' mental health.